Rekonstruksi Hukum Islam terhadap Uang Hantaran di Desa Melibur Kecamatan Talang Muandau Kabupaten Bengkalis Provinsi Riau - Anju Amelia; Nofiardi; Selvi; Nandita (JURNAL ILMIAH PENDIDIKAN KEBUDAYAAN DAN AGAMA, 2026)
The tradition of marriage gift money (uang hantaran) in the Malay community of Melibur Village, Talang Muandau District, Bengkalis Regency, Riau Province, remains a customary practice preserved as a symbol of respect for the bride’s family and a sign of the groom’s seriousness. However, over time, its meaning has shifted toward materialism, as the amount is often determined by social status, educational background, and family prestige, potentially causing economic burdens, psychological pressure, delays, and even the cancellation of marriages. This study aims to describe the practice of uang hantaran and formulate an Islamic legal reconstruction of the tradition in accordance with the principle of simplicity. This research is a field research employing a qualitative approach. Data were collected through interviews, observations, and documentation, and were analyzed descriptively and analytically using the maslahahmursalah approach in Islamic law. The findings indicate that the practice of uang hantaran in Melibur Village is still maintained as part of local custom; however, its implementation has shifted from a symbolic function to a materialistic one, resulting in economic pressure on the groom’s family, psychological burdens on prospective spouses, and delays in marriage. From the perspective of maslahahmursalah, uang hantaran may be categorized as maslahahhajiyyah when determined flexibly and without imposing hardship, but it becomes mafsadah when the amount is excessive and causes harm. Therefore, the reconstruction of Islamic law regarding this tradition emphasizes that uang hantaran is not a legal requirement for marriage but rather a complementary customary practice whose determination should be based on deliberation, mutual consent, economic capability, and the principle of simplicity (taysir), so that it does not hinder the objectives of marriage in Islam.